Analysis of Underseepage Phenomena of River Po Embankments. (2016) - Martínez, María Fernanda García; Gragnano, Carmine Gerardo; Gottardi, Guido; Marchi, Michela; Tonni, Laura; Rosso, Alessandro
Abstract: The Po River (Northern Italy) is the longest watercourse in Italy and over half of its length is safeguarded by major river embankments. Their stability is crucial for the local communities, being the Po River plain densely populated. Among all possible failure mechanisms, backward erosion piping at the interface between the bottom sandy aquifer and the overlying fine-grained soils has proved to be one of the most threatened phenomena. This paper describes the reactivation of a sand boil in a river embankment section in the Province of Ferrara, during the 2014 major high-water event. Detailed stratigraphic soil profiling as well as careful geotechnical characterization of the embankment and of the subsoil have been carried out on the basis of in-situ tests. Then, safety assessment of the backward erosion piping has been performed using simplified prediction tools and a preliminary 2D numerical model. Results are compared and discussed with the aim of providing some insight into the mechanism under investigation.